(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The rapid evolution of artificial intelligence has entered a decisive phase characterized by the emergence of agentic systems capable of autonomous reasoning, decision-making, coordination, and execution across complex digital environments. Within this paradigm, agentic artificial intelligence orchestration frameworks have become central to enterprise-scale transformation, particularly in composable digital ecosystems where modular services, distributed intelligence, and adaptive governance intersect. This research article presents a comprehensive theoretical and empirical investigation into agentic AI orchestration within composable commerce and enterprise ecosystems, situating contemporary developments within broader traditions of distributed artificial intelligence, multi-agent systems, and organizational transformation theory. Drawing extensively on recent scholarly contributions in large language model agents, agent protocols, reasoning-and-acting architectures, and enterprise AI deployment challenges, this study advances a unified conceptual framework that integrates technical architectures with organizational, ethical, and governance dimensions. The study adopts a qualitative, interpretive research methodology grounded in comparative literature synthesis and analytical abstraction. Through a detailed examination of agentic orchestration mechanisms, memory-enhanced agents, agent-to-agent communication protocols, and reinforcement-driven reflexive learning systems, the research elucidates how agentic AI enables composability, resilience, and strategic agility in enterprise environments. Particular emphasis is placed on orchestration frameworks that coordinate heterogeneous agents across commerce, logistics, finance, and decision-support domains, highlighting how agent autonomy and centralized governance are dynamically balanced. The analysis critically engages with contemporary debates on scalability, trust, accountability, and ethical risk, demonstrating how agentic systems challenge traditional managerial and computational assumptions. Empirical insights are derived from documented enterprise transformation cases and sectoral analyses, with particular attention to orchestration frameworks that operationalize agentic AI in real-world composable commerce settings. The findings suggest that agentic AI orchestration is not merely a technological innovation but a socio-technical reconfiguration that reshapes organizational boundaries, labor relations, and strategic decision-making processes. The results further indicate that enterprises adopting agentic orchestration frameworks achieve higher adaptability, faster innovation cycles, and improved systemic coherence, while simultaneously confronting intensified governance and ethical complexity. The discussion synthesizes these findings into a multi-layered theoretical contribution that bridges artificial intelligence research, enterprise architecture, and organizational theory. By articulating design principles, governance imperatives, and future research trajectories, this article contributes a foundational reference for scholars and practitioners seeking to understand and implement agentic AI orchestration in composable digital ecosystems.